Author Correction: Microbial temperature sensitivity and biomass change explain soil carbon loss with warming. Issue 11 (November 2018) - Walker, Tom; Kaiser, Christina; Strasser, Florian; Herbold, Craig; Leblans, Niki; Woebken, Dagmar; Janssens, Ivan; Sigurdsson, Bjarni; Richter, Andreas
In the version of this Letter originally published, the name of the institute in affiliation 3 was incorrect; it read "Institute of Applied Systems Analysis" but should have read "International Institute for Applied Systems Analysis". This has now been corrected.